Talang Semut in the Urban Dynamics: A Study of Morphological Changes and Area Development - Sumarwoto, Imam; Mentari, Rafi; Aisha, Sarah (Lakar: Jurnal Arsitektur, 2025)
The Talang Semut area in Palembang has a long history, beginning in 1933 during the Dutch colonial era. Designed by Ir. Thomas Karsten, this area was initially intended as an elite residential neighborhood, following the principles of the Garden City concept that prioritized green spaces, wide main roads, and a non-clustered arrangement of buildings. Although it has undergone significant changes, particularly in terms of function and population density, the area still retains its heritage characteristics, including colonial architecture and a well-structured urban layout. This study aims to identify the changes in the Talang Semut area, focusing on physical, social, and economic aspects, by comparing the conditions of the area in the past and present. The analysis reveals that the major challenges faced by this area include urbanization, changes in building functions, and pressures on green spaces. However, the ongoing development dynamics reflect the area's adaptation to the growing demands of the city, such as the modernization of public facilities, improved accessibility, and the preservation of historical values. This research provides recommendations to pay more attention to cultural heritage preservation, planned urbanization management, and community empowerment in maintaining a balance between modern development and the conservation of Talang Semut's historical heritage.